Impacto do auxílio estudantil sobre a evasão e aprovação escolar: Uma análise dos CAMPI do IFCE que compoem a região metropolitana de Fortaleza entre 2013-2014 - Pinho, José Adriano Carvalho de (2017)
One of the main concerns of education policy makers is to reduce dropout rates and failure of students. Investigate the causes of evasion and to develop educational policies to control this problem are among the leading research agendas of the studies related to the subject. To control truancy, the IFCE offers a number of aid to their students as a way to motivate them to attend classes and increase their academic performance. The main objective of this work is to verify that such aid would have worked significantly in reducing truancy and increasing adoption of the students in the period 2013-2014. With a sample of students benefited (treatment group) and not benefit (control group) the vocational technical high school level of IFCE on the campuses of Fortaleza, Caucaia and Maracanaú, we attempted to quantify the impact of granting the aid policy on evasion and approval by the methodology of the model differences in differences for the years analyzed. The results point to a reduction in dropout this level of education, i.e., the granting of aid to IFCE students had a negative and statistically significant effect on truancy. For the approval, the results indicate a positive impact of aid policy on the approval of students in vocational medium level IFCE. Keywords: Dropout.